Chemical analysis and protective effect of Elaeis guineensis kernel oil against calcium ion-induced mitochondrial membrane permeability transition (Journal of Basic and Applied Research in Biomedicine, 2022)
This study evaluated the chemical property and effect of Elaeis guineensis kernel (EGK) oil on calcium ion-induced mitochondrial membrane permeability transition (MMPT) using standard in vitro methods. Results showed the EGK oil values for iodine (46.53±1.8 Wij’s), saponification (246.33±1.2 mgKOH/g), acid (10.32±2.5%) and peroxide (3.03±0.4 mEq/kg). EGK oil (150 µg/ml) exhibited a maximal inhibitory (80.9±4.8%) effect on MMPT. Furthermore, EGK oil (100 µg/ml) maximally stabilized (96.72±5.2%) erythrocyte membrane against hypotonicity-induced hemolysis. In addition, EGK oil (250 µg/ml) inhibited heat-induced protein denaturation by 12.42±2.6% and mitochondria lipid peroxidation by 61.03±3.7%. This study showed that EGK oil could possess mitochondria protective agent(s).